On the fatigue life enhancement due to periodic healing of a NiTi shape memory alloy - Shastry, V. V. (2022)
Fatigue failure in NiTi based shape memory alloys (SMAs) that are in the austenitic state is accelerated by the progressive accumulation of stress-induced martensite (SIM) under cyclic loading, even when the maximum stress of the fatigue cycle is well below that required for stress-induced martensitic transformation. Wagner et al. (2008) [1] have shown that periodic annealing of the fatigued specimens at temperatures well above the austenitic finish temperature, which they termed as ‘healing’, can enhance the fatigue life of the SMAs that are cyclically loaded in the austenitic state. In this paper, the optimum interval at which healing must be performed is investigated. Experimental results show that considerable improvement in the total life of the SMA component can be realized if the fatigued specimens are healed periodically right after 20% of their service life has lapsed. Healing later (at 40% and 60% of the fatigue life) does not lead to any significant improvement, indicating that irreversible damage has already set in. Real-time infrared thermography technique was used to study the thermal signatures during tensile and fatigue testing. Results show that it is possible to monitor the formation of SIM during cyclic loading using thermography.